realisasi tindak kesantunan imperatif pada jargon warung makan di wilayah surakarta - utari, siti, Prof. Dr. H. Abdul Ngalim, MM, M.Hum, Drs. Yakub Nasucha, M.Hum (2015)
The purpose of this study is twofold. 1) Describe the type of follow politeness imperative in the jargon of the food stalls in the area of ​​Surakarta. 2) Describe the form of acts of politeness imperative in the jargon of the food stalls in the area of ​​Surakarta. The data required in this research that jargon food stalls in the area of ​​Surakarta. Source data from this study is twofold. 1) Sources of primary data in this study is jargon food stalls in Surakarta. 2) Secondary data sources in this study is the thesis, books, websites, research relevant to this study. This research is descriptive qualitative, because the data obtained is not poured in the form of numbers or statistics, but rather a description of the object and the results of the study in the form of a narrative. Data collection techniques and engineering using techniques refer to note. Through a technique to listen to and record the theories used in the study, and then arranged in sequence so as to form a harmonious composition to compile research findings. That is the data found in the object of the study listened to then be recorded and grouped by formulation problems. This study uses contextual data analysis. Before performing data analysis grouped in advance in order to obtain the appropriate form and manner. In this way is expected to simplify the analysis process. Results of this study 1) The form of politeness imperative in the jargon of the food stalls in the area of ​​Surakarta found 8 data in the form of politeness imperative that includes imperative usual (2 data), the imperative demand (2 data), imperative licensing (1 data), imperative messenger (2 data). 2) Being politeness imperative found in this study there are 18 data in the form of politeness imperative that include a form of formal pragmatic imperatives (3 data) includes the imperative of active / imperative active transitive (1 data) and the imperative of passive (2 data) and a form of pragmatic imperatives ( 15 data.